VOICE AND FREQUENCY IN QUENTIN TARANTINO’S PULP FICTION MOVIE SCRIPT - Sandy Agung; Dadan Rusmana; Lili Awaludin (Universitas Islam Negeri Sunan Gunung Djati, 2020)
This research discusses the narrative discourse structure in Quentin Tarantino’s Pulp Fiction movie script. Pulp Fiction (1994) Pulp Fiction is known as one of the best crime and drama genre movie. Pulp Fiction directed by Quentin Tarantino. Quentin Tarantino and Roger Avery wrote the script. The movie presented many drops of blood, fights, and gun in the scenes. This movie also provides us with many “nigga” words. The researcher used Gerrard Genette’s narrative discourse theory. This study was conducted into two research problem; 1. What are the kinds of voice that consist in Quentin Tarantino’s Pulp Fiction movie script? 2. What are the kinds of frequency that consists in Quentin Tarantino’s Pulp Fiction movie script? The result of this research shows that in this movie there are two kinds of voice. Moreover, there are some data that show frequency that exist in Quentin Tarantino’ Pulp Fiction movie script.